2014
DOI: 10.1021/jp508279n
|View full text |Cite
|
Sign up to set email alerts
|

Redox Properties of Graphenes Functionalized with Cyclopentadiene–Transition Metal Complexes: A Potential Redox-Active Material

Abstract: The redox properties of CpTM (Cp = cyclopentadienyl and TM = transition metal) on B-doped, N-doped, and pristine graphene complexes are evaluated using density functional theory in order to determine the possibility of using these complexes as novel redox-active materials for electrochemical applications. The CpFe/B-doped graphene complexes with a series of different sidechains are found to have comparable redox potentials to ferrocene molecules and other ferrocene-based electrochemical sensors (in water and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Turing the electrochemical property of carbon nanomaterial by structure–activity relationship is a cutting-edge research in material science. Graphene, a wonderful two-dimesional (2D) material, with a honeycomb lattice-like sp 2 carbon structure differing distinctly from that of other carbon allotropes like diamond, has emerged as an advanced carbon nanomaterial for electronic devices, biomedicals, conducting materials, and mechanical systems owing to its extraordinary physical properties like high surface area, thermal and electrical conductivity, and mechanical strength. Electron-transfer (ET) reaction is one of the important physical properties that have been achieved in graphene after functionalized with oxygen, metal, metal complex, and redox-active organic species. Although there has been a significant number of reports on the electrochemical activity of graphene and its related materials, the pristine-graphitized mesoporous carbon material (GMC) is never reported for any redox activity. Herein, we observe an intrinsic electron-transfer activity of a graphene molecular model, coronene (Cor), after being π-self-assembled on graphitic materials like graphite, multiwalled carbon nanotube (MWCNT), single-walled carbon nanotube (SWCNT), and graphitized mesoporous carbon material (GMC).…”
Section: Introductionmentioning
confidence: 99%
“…Turing the electrochemical property of carbon nanomaterial by structure–activity relationship is a cutting-edge research in material science. Graphene, a wonderful two-dimesional (2D) material, with a honeycomb lattice-like sp 2 carbon structure differing distinctly from that of other carbon allotropes like diamond, has emerged as an advanced carbon nanomaterial for electronic devices, biomedicals, conducting materials, and mechanical systems owing to its extraordinary physical properties like high surface area, thermal and electrical conductivity, and mechanical strength. Electron-transfer (ET) reaction is one of the important physical properties that have been achieved in graphene after functionalized with oxygen, metal, metal complex, and redox-active organic species. Although there has been a significant number of reports on the electrochemical activity of graphene and its related materials, the pristine-graphitized mesoporous carbon material (GMC) is never reported for any redox activity. Herein, we observe an intrinsic electron-transfer activity of a graphene molecular model, coronene (Cor), after being π-self-assembled on graphitic materials like graphite, multiwalled carbon nanotube (MWCNT), single-walled carbon nanotube (SWCNT), and graphitized mesoporous carbon material (GMC).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, using first-principles calculations, we systematically investigate the structural, electronic and magnetic properties of half-sandwiched organometallic CpTM (TM = Sc-Ni) functionalized bilayer graphene, CpTM@BLG. The choice of CpTM ligands as the functionalization ligands is due to the following advantages: (1) the synthesis of such organometallic sandwich structures has been well established, such as CpTM/fullerene, 41,42 Bz/Cr/CNT or graphene, 43 and CpTM/sumanene; 44 (2) studies have demonstrated that the binding of CpTM with graphene is rather stable; 45,46 (3) compared with the functionalization of graphene with pure transition metal atoms, the Cp ligands can effectively prevent the clustering of metal particles on the surface of graphene besides the introduction of magnetic moments into the system. Our calculations show that the CpTM ligands interact strongly with the graphene layer by covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the electron is transferred from the metallocene headgroups to the underlying conducting surface by a tunneling process across the monolayer. On account of this, the surface chemistry of metallocenes has been studied for different applications . In general, ferrocene, [Fe(C 5 H 5 ) 2 ], is a well‐known system for a class of three‐dimensional metallocene molecules, and adsorption experiments of the ferrocene on metal surfaces have been performed for different applications .…”
Section: Introductionmentioning
confidence: 99%
“…On account of this, the surface chemistry of metallocenes has been studied for different applications. [5][6][7][8][9][10][11][12] In general, ferrocene, [Fe(C 5 H 5 ) 2 ], is a well-known system for a class of three-dimensional metallocene molecules, and adsorption experiments of the ferrocene on metal surfaces have been performed for different applications. [13][14][15] Tegenkamp et al reported the chemisorption of thiol-modified ferrocene molecule on Si(111)-Agͱ33ͱ3 surface.…”
Section: Introductionmentioning
confidence: 99%